Pengaruh Pemberian Teknik Range Of Motion (Rom) Terhadap Kekuatan Otot Pada Pasien Stroke Non Hemoragic (Snh) - Herlina; Fajar Yudha; Septi Kurniasari; Yoga Nicolas Pradipta (STIKes IMC Bintaro, 2023)
Introduction Stroke sufferers can recover completely if treated within the first 6 hours (the golden period), but if it is too late, long-lasting disability or physical weakness can occur. To reduce the sequelae of stroke, in addition to being done with physiotherapy, ROM (Range of Motion) exercises can be done. The ROM technique is a series of simple exercises to increase muscle strength. The purpose of this study was to determine the effect of giving the ROM technique on the muscle strength of stroke patients. Quasi-experimental research design pre and post test design with a total sample of 26 people and purposive sampling technique. Data were collected using observation sheets and univariate and bivariate data analysis. The results showed that before the ROM intervention most of the SNH patients with